Screening Method for Assessment of Work Ability for Patients Suffering From Mental Fatigue - Johansson, Birgitta (Frontiers in Behavioral Neuroscience, 2022)
Pathological mental fatigue adversely affects endurance in the performance of tasks over time, with negative impact on work ability and can exist without significant neurological or cognitive impairment. There are currently no methods for objectively assessing work ability for patients suffering from mental fatigue. In this study, work ability in relation to mental fatigue as a screening method was evaluated, using the Work Ability Index (WAI) and Mental Fatigue Scale (MFS). Included participants represented three patient groups commonly affected by mental fatigue; acquired brain injury (n=49, traumatic brain injury, stroke), burn-out syndrome (55) and hypothyroidism (50). The results showed a significant relationship between WAI and MFS (r=-0.754) and status in the workplace (WAI r=0.722), MFS r=-0.443) for all groups, and WAI and MFS were significant predictors for status in the workplace (p <0.001) and explained 53% of the variance. This screening method can help health care professionals to identify people who are mentally fatigued with a reduced ability to work or return to work after illness, and who are in need of in-depth investigation. It is important to initiate treatment early with the aim of promoting a sustainable working life and general well-being of the individual.